An Adaptive Line-of-Sight (ALOS) Guidance Law for Path Following of Aircraft and Marine Craft - Fossen, Thor I. (IEEE transactions on control systems technology, 2023)
This brief presents a novel nonlinear adaptive line-of-sight (ALOS) guidance law for path following, compensating for drift forces due to wind, waves, and ocean currents. The ALOS guidance law is proven to have uniform semiglobal exponential stability (USGES) properties during straight-line path following at constant speed. The ALOS guidance law performs similar to the classical integral line-of-sight (ILOS) and adaptive ILOS guidance laws when the sideslip angle is nearly constant. The ALOS guidance law, however, has better tracking capabilities when compensating for rapidly varying sideslip caused by a time-varying disturbance. This is because the integral state of the ALOS guidance law is additive to the unknown sideslip angle (disturbance matching). In contrast, the ILOS guidance laws must compensate sideslip through a saturating arctangent function. The study also includes an input-to-state stable (ISS) reduced-order extended state observer for estimation of the line-of-sight (LOS) crab angle, known as the ELOS guidance law. The performance of the ALOS, ILOS, and ELOS guidance laws is compared by simulating rapid changes in the sideslip angle to stress the critical assumptions of the algorithms. Finally, a case study of the Remus 100 autonomous underwater vehicle (AUV) exposed to stochastic ocean currents is used to compare the performance of the ILOS, ALOS, and ELOS algorithms during normal operation.